Transitions in Postcoloniality as a Revolutionary Thought across the Subject Societies - Najar, Mudasir Rahman (American International Journal of Social Science Research, 2019)
There has to be the necessary change across the pages of history amongst the various fields of knowledge in our social structure. In this context, there has been emergence of a thought that went contrary to the established thought of colonial propaganda. This counters colonial discourse no doubt too many years to have its roots strong in the soil of social, cultural, and psychological phenomena of our society. Though, literary theory, in general, is a way of understanding the nature and function of literary creation. It seeks the relation of a text to the author and to the society by presenting a thesis or the antithesis in literary field that in turn speaks for social forces. This means to evaluate, to elucidate and to interpret the literary processes for the social discourses have always been very effective for the social change. This directly or indirectly leads the effected society to get changed in terms of thinking process. Hence, leads to the intellectually rich and psychologically mature civilization.